Shear bond strength of three self-adhesive resin cements to dentin - Asefzadeh Farrokh; Merati Mohsen; Salari Soheil; Bashardoost Nazanin (Wolters Kluwer Medknow Publications, 2012)
Context: The result of the studies concerning the bonding of self-adhesive resin cements to dentin is controversial. Aims: To assess in vitro shear bond strength (SBS) of three self-adhesive dual-cured resin cements to dentin compared to a currently used dual-cured resin cement, using SBS test. Settings and Design: The extant study is an experimental in vitro one on extracted human third molars dentin. Material and Methods: 40 intact human third molars were selected and randomly divided into 4 groups of 10. Buccal dentin surfaces were exposed perpendicular to the long axis and prepared with SiC papers. A translucent plastic ring, was placed over the dentin surfaces. Group I (Control group): After 15 s of etching and application of Excite DSC Bond (Ex), Variolink II (Var II) resin cement was injected into the plastic ring and was light cured for 40 s. Group II: RelyX Unicem (RX) was injected into the plastic ring and after 30 s, was light cured for 40 s. Group III: Maxcem (Mc) was injected into the plastic ring and after 30 s, was light cured for 40 s. Group IV: Multilink Sprint (MS) was injected into the plastic ring and after 30 s, was light cured for 40 s. After thermal cycling, SBS were measured with a universal testing machine. Statistical Analysis Used: Statistical computations were conducted according to Student's t-test. Results: The mean SBS and standard deviations (in parentheses) for groups I, II, III, and IV were 12.95 (2.64), 6.73 (0.79), 3.01 (0.90), 4.60 (0.75) MPa, respectively. Statistical analysis, revealed that: (1) the mean SBS of Var II were significantly higher than the other groups (P<0.05). (2) The mean SBS of Mc and MS were significantly lower than RX (P<0.05). (3) The mean SBS of Mc and MS did not show significant difference (P>0.05). Conclusion: Bond strength of three self-adhesive resin cements was significantly lower than the conventional total-etch resin cement. RX significantly performed better SBS than Mc and MS to dentin.